Cenozoic Palaeogeography of Africa: from Mantle Dynamic to Source-to-Sink Systems - (:unkn) unknown (My University, 2022)
To test the mantle dynamic control in this topographic pattern of Africa and to discuss their effects on the relief growth and their consequences on the source-to-sink systems, we compiled new style palaeogeographic maps at Africa-scale with a first attempt of palaeotopographic reconstructions and quantification. These observations suggest that the South African superplume had a significant role in the growth of these topographies since 40 Ma, with a propagation of the superplume toward the north and a progressive spreading below the North African lithosphere during the locking of Africa Plate with Eurasia Plate. The initiation of the uplift at 40 Ma localized the erosion along the “coastal” plains, enhanced from 40 Ma to today by isostatic rebounds and modulated by plate-scale deformation and/or major climatic changes.
Keywords: African Research